Fumigant Activity of Eight Plant Essential Oils Against Workers of Red Imported Fire Ant, Solenopsis invicta - Liang Tang (Universidade Estadual de Feira de Santana, 2013)
Plant essential oils from eight plant species were tested for their insecticidal activities against the red imported fire ant, Solenopsis invcita, by using a fumigation bioassay. This study reveals that the mortalities after treatment of the workers of red imported fire ants varied according to the classification of workers, oil type, dosage, and exposure time. Among the essential oils tested, strong insecticidal activity was observed with the essential oils of camphor (Cinnamomum camphora), artemisia annua (Artemisia annua), eucalyptus (Eucalyptus globulus), mugwort (Artemisia argyi), and wintergreen (Ilex chinensis). Ant mortalities from chrysanthemum oil (Dendranthema indicum), turpentine oil (Pinus massoniana), and forsythia oil (Forsythia suspense) treatments were significantly lower than those from the previously mentioned five essential oil treatments. This study showed that camphor, artemisia annua, eucalyptus, mugwort, and wintergreen oils may have potential to be used as substitutes for chemical insecticides.